Buerger's disease: early detection to minimize progression - Agus Santosa; Ritma Ratri; Surtiningsih Surtiningsih (Medisains, 2022)
Background: Delays in the diagnosis of Buerger's disease are common. Its rare cases and lack of information about risk factors and signs and symptoms of the disease are thought to be the causes. This study aims to report and discuss findings of delays in the diagnosis of Buerger's disease cases experienced by two patients over many years.